Legal and Administrative Environment of Inclusive Libraries for People with Disabilities in Lithuania - Kulikauskienė, Kristina; Liukinevičienė, Laima (Information & Media, 2020)
The article analyzes the provisions of the most important international and national documents obliging public libraries to contribute to the reduction of social exclusion by meeting the informational, cultural and social needs of people with disabilities. The analysis of scientific literature reveals that the process of social inclusion requires changes in library activities and is associated with innovation. This process demands appropriate management, while the implemented changes should include activities associated with the key elements of an inclusive library – organizational management, accessibility of library services and environment, improved staff competences, collaboration with organizations representing disabled people and promotion of services. The article presents the results of the analysis of activity documents (2014-2019 annual activity plans and reports) of Šiauliai region libraries. This analysis enables to assess the readiness of libraries to become inclusive organizations for people with disabilities and to evaluate the current situation of initiation, implementation and consolidation of activities related to library services for people with disabilities from the perspective of change management.